Interfaith Marriage in Salatiga (Indonesia) and Yala (Thailand): Legal Constraints, Social Realities and Human Rights Implications (Program Studi Hukum Keluarga Islam, 2025)
Salatiga City in Indonesia and Yala Province in Thailand are known for their multicultural and multireligious people. Both show complex social dynamics in dealing with religious issues, including the practice of interfaith marriage. This study aims to: (1) describe the practice of interfaith marriage in Salatiga and Yala; (2) analyze the differences and similarities in the perspectives of Islamic law and state law in both regions on interfaith marriage; and (3) examine the responses of human rights activists to this phenomenon in their respective social and cultural contexts. The method used is qualitative research with a juridical-empirical approach and legal comparison. Primary data was obtained through interviews with Islamic religious leaders, human rights activists, and representatives of Non-Governmental Organizations (NGOs) in Salatiga and Yala. In Salatiga, the practice of interfaith marriage is generally facilitated by NGOs such as Percik who provide assistance and education to couples. In Yala, which is Thailand's Muslim-majority region, interfaith marriages also occur albeit in a more closed social sphere, and are more influenced by conservative Islamic norms and a dualistic legal system between state law and local Islamic law (Sharia). Responses from human rights activists in both regions have also varied. Most of them say that individual freedom in choosing a life partner is part of the human rights that the state should guarantee. This research confirms that interfaith marriage is not only a legal issue, but also a reflection of identity dynamics, pluralism, and the tension between individual rights and collective norms in multicultural societies.